Critical information as a success factor in organizations: objective and methodological approach - Fernandes, Silvia Brito (2012)
We are witnessing the need for a quick and intelligent reaction from organizations to the level and speed of change in business processes. These imperatives are very often associated to the emerging of new information systems and technologies, sometimes bursting change and other times being burst, which bring more challenges to organizations. The arising problems can be: from wrong information that lasts; systems not fully used or explored; too much staff; slow reaction to change; etc. This can be summarized in a governance problem that requires two main confluent action methods: people to synchronize their visions, ideas and strategies in the whole organization; and, in that context, select the information that strictly answers to the performance factors at the right moment. The proposed methodology is adequate here, once it turns to the potential of approach to the entrepreneurial architecture as well as to the potential of the information system in order to iteratively select and integrate the data and resources needed for that performance. The modeling of an information architecture of the company and its business helps in the identification of critical information, that is, of the one which is according to the mission, prospects and critical factors of business success at the required moment.